Scholastic Pocket Dictionary. - Scholastic Reference (Firm) (New York : Scholastic, 2005)
Dictionary of English language, A-Z; Grammar guide; Punctuation guide; Idioms guide; Intials, Acronyms, and abbreviations guide
Basic ed. students
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries